Variability for Functional and Nutritional Quality Traits in Sweet Pepper (Capsicum annuum L.) - N K Hedau (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2013)
Natural biodiversity for functional and nutritional quality traits is of prime importance in breeding programmes for developing nutritionally rich genotypes. The present investigation was carried out to identify lines of sweet pepper with high ascorbic acid content and important mineral nutrients like potassium, phosphorus, zinc, copper, iron and manganese. Forty accessions of sweet pepper (Capsicum annuum L.) were analyzed for their functional and nutritional composition. Wide variation was observed in functional quality traits like ascorbic acid content (22-129mg 100g-1), and β-Carotene (0.39-1.0mg 100g-1) suggesting a considerable level of genetic diversity. Wide variability was also noticed for nutritional composition (K, P, Zn, Cu, Fe&Mn) in the tested lines. Across accessions, concentration of ascorbic acid was negatively correlated with copper content (r = -0.293, p < 0.05) being significantly greater in two accessions, VHC 34 and VHC 37 (129 and 118.0 mg100g-1, respectively) compared to other accessions. β-Carotene concentration was higher (0.85 to 0.99mg 100g-1) in six accessions, and lower (0.39 to 0.54mg 100g-1) in twenty four accessions. Greater variability present for quality traits holds an immense potential to help develop Capsicum lines with traits of high functional and nutritional quality. Therefore, this information is potentially useful in sweet pepper breeding programmes in the future.